Community-Based Development of Adaptive Digital SOPs for Hydroponic Farming at BGD Hydrofarm - Fazrol Rozi; Yance Sonatha; Fitri Nova; Primawati Primawati; Muhammad Ridwan Kurniawan (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2026)
Background: Community-based hydroponic farming at BGD Hydrofarm faces challenges including manual monitoring, static Standard Operating Procedures (SOPs), and limited digital literacy, which reduce operational efficiency and accuracy. This community service program addresses these issues through the introduction of adaptive digital technologies. Purpose of the Study: This study aims to improve hydroponic management practices and strengthen community capacity by co-developing adaptive digital SOPs that support data-driven decision-making at BGD Hydrofarm. Methods: A participatory approach was applied, including needs assessment, co-design sessions, system development, training workshops, and participatory monitoring and evaluation. The GardenKeeper system integrates IoT-based sensors (monitoring pH, TDS, temperature, humidity, and plant visual condition) with generative artificial intelligence (Google Gemini AI) to provide real-time monitoring and adaptive SOP recommendations via a mobile application. Results: The program resulted in reduced manual workload, improved monitoring efficiency, and increased partner confidence in using digital technology. Behavioral shifts from experience-based to data-driven decision-making were observed, with SOP consultations becoming a shared reference for collective action. Partners independently operated the application, and external stakeholders (Ministry of Cooperatives and SMEs, IGES) recognized the system's potential scalability. The before-after comparison showed improved digital confidence, reduced operational errors, and strengthened collaborative decision-making.